An Analysis of Emotion Space of Bra by Kansei Engineering Methodology (Journal of Fiber Bioengineering and Informatics, 2018)
In this study, the technique of Kansei engineering was used to assess the emotion space of bra. Sixtystyles of Wacoal high-quality bra were regarded as stimuli. Fifteen pairs of adjectives and four pairs ofphases on color, pattern, style, preference were selected to prepare the questionnaire according to theSemantic Differential method: “modern-classical”, “vulgar-noble”, “charming-charmless”, “intellectual-rustic”, “painted-refreshing”, “active-serious”, “restrained-inflated”, “luxury-frugal”, “lovely-unlovely”,“personality-popular”, “cumbersome-simple”, “sweet-not sweet”, “romantic-actual”, “mature-naive”,“sexy-not sexy”, “good color-bad color”, “good pattern-bad pattern”, “good style-bad style”, and “like-dislike”. Five scales were set for each pair of phase. The survey was conducted among the undergraduatecollege students from Xi'an Polytechnic University. The data from the survey were analyzed using factoranalysis and cluster analysis. Four factors were extracted and labeled as “personality”, “age”, “taste”,“fashion”. The results also indicated that color was the most important factor when designing a bra,especially the base color of the bra, which decided the basic emotion of the bra.